Search for anomalous single top quark production in association with a photon in pp collisions at √s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Eroe, J.; Flechl, M.; Friedl, M.; et al. (SPRINGER, 2016)
The result of a search for flavor changing neutral currents (FCNC) through single top quark production in association with a photon is presented. The study is based on proton-proton collisions at a center-of-mass energy of 8 TeV using data collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 19.8 fb(-1). The search for t gamma events where t -> Wb and W -> mu nu is conducted in final states with a muon, a photon, at least one hadronic jet with at most one being consistent with originating from a bottom quark, and missing transverse momentum. No evidence of single top quark production in association with a photon through a FCNC is observed. Upper limits at the 95% confidence level are set on the tu gamma and tc gamma anomalous couplings and translated into upper limits on the branching fraction of the FCNC top quark decays: B (t -> u gamma) c gamma) < 1.7 x 10(-3). Upper limits are also set on the cross section of associated t gamma production in a restricted phase-space region. These are the most stringent limits currently available.
Keywords: Flavour Changing Neutral Currents; Hadron-Hadron scattering (experiments); Top physics; PARTON DISTRIBUTIONS; HADRON COLLIDERS; DECAYS; Physics